Systematic Literature Review: Peran Chatgpt dalam Pembelajaran Matematika Berbasis Problem Based Learning terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Loria Natalia Br Depari; Ni Nyoman Parwati; Kadek Ayu Mutiara Pratiwi; I Made Ardana; Gusti Ayu Mahayukti (Dharma Acariya Nusantara Jurnal Pendidikan Bahasa dan Budaya, 2026)
This study aims to examine the role of ChatGPT in Problem Based Learning (PBL)-based mathematics learning on students’ mathematical problem-solving abilities. The method used is a Systematic Literature Review (SLR) following the PRISMA protocol. Data were collected from articles indexed in Google Scholar and Semantic Scholar, published between 2020 and 2026. Based on a rigorous selection process involving identification, screening, and eligibility stages, 11 articles met the inclusion criteria. The findings indicate that the PBL model consistently improves students’ mathematical problem-solving abilities by encouraging active engagement, critical thinking, and independent learning. Furthermore, the integration of Artificial Intelligence (AI), particularly ChatGPT, contributes positively by supporting conceptual understanding, providing alternative solution strategies, and enhancing students’ learning motivation. The results also show that the combination of PBL and ChatGPT has greater potential in improving mathematical problem-solving skills compared to their separate implementation. However, challenges such as technology dependency and information accuracy still exist. Therefore, the integration of PBL and ChatGPT can be considered an innovative learning approach in 21st-century mathematics education.